2018
DOI: 10.1111/joor.12634
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the oral health status and oral hygiene practices according to the extent of post‐stroke sequelae

Abstract: Oral health and hygiene are crucial parameters in stroke patients. However, few studies have evaluated the oral health status and oral hygiene practices according to the level of function in stroke patients. The aim of this study was to evaluate the oral health status and oral hygiene practices according to ambulation and personal hygiene levels in patients with stroke. Data from the fifth (2010-2012) and sixth (2013-2015) editions of the Korea National Health and Nutrition Examination Survey (KNHANES) for 6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Previous studies indicate a link between oral health and general condition of stroke patients. It has been demonstrated that subjective oral health was significantly poorer in stroke cases (such as tooth loss and dental caries experience), according to ambulation level and functional independence [23]. Additionally, some studies have shown a relationship between periodontal disease and the occurrence of strokes [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate a link between oral health and general condition of stroke patients. It has been demonstrated that subjective oral health was significantly poorer in stroke cases (such as tooth loss and dental caries experience), according to ambulation level and functional independence [23]. Additionally, some studies have shown a relationship between periodontal disease and the occurrence of strokes [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, caries is likely the cause of poor oral health. Comparatively, this situation is even worse in stroke patients [35]. From the results above, dental caries plays an important negative role (OR = 1.292) in the abnormal oral cleanliness of acute ischemic stroke patients (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…This could be attributed to the fact that stroke survivors who had undergone rehabilitation treatment and had higher functional levels enjoyed a better oral health status and OHR-QoL. 31 Most patients reported high confidence despite restrictions on their participation in social activities. However, only a minority of them complained about eating difficulties, most probably arising from oro-facial muscle weaknesses.…”
Section: Discussionmentioning
confidence: 99%